2017
DOI: 10.1111/dme.13290
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25(OH)D3 and cardiovascular morbidity and mortality in people with Type 2 diabetes: a community‐based cohort study

Abstract: Low 25(OH)D is associated with an increased risk of cardiovascular morbidity and mortality in people with Type 2 diabetes independent of parathyroid hormone. Vitamin D could be considered as a prognostic factor. Future studies are needed to explore whether vitamin D deficiency is a modifiable risk factor in Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In line with previously mentioned evidence, in our study survivors of MI with DM and concomitant VitD deficiency had a worse prognosis when compared to those with only DM, hypovitD or neither of them. Samefors et al [58], in a cohort of 698 patients with type 2 DM, found that low 25(OH)D3 is associated with an increased cardiovascular morbidity/mortality. In our population, diabetic patients had worse long-term outcomes when compared to non-diabetic patients, coherently with previously published data [59].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previously mentioned evidence, in our study survivors of MI with DM and concomitant VitD deficiency had a worse prognosis when compared to those with only DM, hypovitD or neither of them. Samefors et al [58], in a cohort of 698 patients with type 2 DM, found that low 25(OH)D3 is associated with an increased cardiovascular morbidity/mortality. In our population, diabetic patients had worse long-term outcomes when compared to non-diabetic patients, coherently with previously published data [59].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that vitamin D has neuroprotective properties [ 20 ] and vitamin D supplementation could be beneficial to reduce the volume of cerebral infarct in animal models of stroke [ 21 ]. Interestingly, another study reported that low 25(OH) D was associated with an increased risk of cardiovascular morbidity and mortality in people with type 2 diabetes independent of PTH [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding alcohol use and smoking habits, no variation was seen. The baseline characteristics regarding age, gender, anthropometric measurements, and laboratory data have been described previously [24]. Spearman's correlation coefficients between 25(OH)D 3 and key continuous variables are presented in Supplementary Table 1.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…We analyzed data from T2D patients aged 55-66 years (n = 761) who participated in a prospective observational community-based cohort study: CARDIPP (Risk factors in Patients with Diabetes-a Prospective study in Primary Care), which has been described previously [22][23][24]. The participants were consecutively recruited from 22 primary health care centers in southern Sweden.…”
Section: Participantsmentioning
confidence: 99%